2013
DOI: 10.1016/j.cmet.2013.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation by p53 Family Members

Abstract: The function of p53 is best understood in response to genotoxic stress, but increasing evidence suggests that p53 also plays a key role in the regulation of metabolic homeostasis. p53 and its family members directly influence various metabolic pathways, enabling cells to respond to metabolic stress. These functions are likely to be important for restraining the development of cancer but could also have a profound effect on the development of metabolic diseases, including diabetes. A better understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
393
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(429 citation statements)
references
References 174 publications
(242 reference statements)
8
393
1
5
Order By: Relevance
“…P53 is a major regulator of apoptosis, senescence, and cell cycle arrest. However, p53 also regulates various enzymes in metabolism and can promote an oxidative metabolism over a glycolytic metabolism [63]. Yet, there is also evidence that certain metabolic targets of p53 such as hexokinase rather promote than inhibit glycolysis [63].…”
Section: Genetic Alterations In Breast Cancer and Their Connection Tomentioning
confidence: 99%
See 1 more Smart Citation
“…P53 is a major regulator of apoptosis, senescence, and cell cycle arrest. However, p53 also regulates various enzymes in metabolism and can promote an oxidative metabolism over a glycolytic metabolism [63]. Yet, there is also evidence that certain metabolic targets of p53 such as hexokinase rather promote than inhibit glycolysis [63].…”
Section: Genetic Alterations In Breast Cancer and Their Connection Tomentioning
confidence: 99%
“…However, p53 also regulates various enzymes in metabolism and can promote an oxidative metabolism over a glycolytic metabolism [63]. Yet, there is also evidence that certain metabolic targets of p53 such as hexokinase rather promote than inhibit glycolysis [63]. Thus, alterations in p53 status might be able to contribute to both, the Warburg metabolism of triplenegative breast cancer and the reverse Warburg metabolism of estrogen receptor positive breast cancer.…”
Section: Genetic Alterations In Breast Cancer and Their Connection Tomentioning
confidence: 99%
“…1 More recent data have challenged this notion by suggesting that the oncosuppressive functions of p53 mainly originate from its ability to regulate metabolism in baseline conditions. [2][3][4] Now, investigators from the Columbia University (New York, NY, USA) identified ferroptosis, an iron-dependent form of necrotic RCD, as an additional mechanism through which stress-activated p53 may maintain organismal homeostasis. 5 Using a cell line stably transduced with a tetracyclineinducible p53-encoding construct, Jiang et al identified solute carrier family 7 (cationic amino-acid transporter, γ+ system), member 11 (SLC7A11), as a novel transcriptional target of p53.…”
mentioning
confidence: 99%
“…This said, a large body of evidence indicates that p53 mediates oncosuppressive functions also by avoiding, rather than responding to, the potentially oncogenic degeneration of cellular functions. [2][3][4] Most likely, the robust tumor-suppressive activity of p53 reflects its unique ability to preserve both cellular and organismal homeostasis (Figure 1). Figure 1 Oncosuppressive functions of p53.…”
mentioning
confidence: 99%
“…12 It has become increasingly evident that p53 is able to modify a variety of metabolic pathways, including glycolysis and oxidative phosphorylation, enabling cells to respond to metabolic stress. [13][14][15][16][17] Further, p53 is essential for cell survival under glucose deprivation and in tumour cells under metabolic stress is able to augment apoptosis. 13,16 Some studies have even suggested that the ability of p53 to act as a tumour suppressor may be influenced by its role in metabolic regulation, rather than its ability to influence apoptosis, senescence or cell cycle arrest.…”
mentioning
confidence: 99%